Novel bio-inspired fabrication of BiVO4 nanoparticles and their solar light-aided photocatalytic activity for metronidazole antibiotic degradation - Abhale, Yogita; Patel, Kajalben; Paul, Ruhit Kumar; Mishra, Soumya Ranjan; Roy, Saptarshi; Ahmaruzzaman, Md; Ban, Tan Kar; Kumar, Deepak; Ghotekar, Suresh (Springer, 2025)
A popular natural sweetener with a long history of ethnomedical uses dating back to ancient civilizations, honey is a viscous liquid with an amber tint noted for its abundance of bioactive components. This investigation used a honey solution containing bioactive phytoconstituents to create bismuth vanadate nanoparticles (BiVO4 NPs) for the first time. XRD, UV-Vis, FTIR, TEM, SAED pattern, SEM, EDX mapping, XPS, EIS, and BET studies highlighted the physicochemical features of as-prepared BiVO4 NPs. XRD verified the biogenic synthesis of NPs, demonstrating a monoclinic scheelite structure with single-phase purity in the produced material. FTIR peaks at 1315 cm‒1 and 1148 cm‒1 indicate protein structures in the green source-mediated BiVO4 NPs. Biosynthesized BiVO4 NPs exhibit a quasi-spherical morphology with a median particle size of 25.74 nm. Moreover, the photocatalytic efficacy was disclosed by assessing the degradation rate of metronidazole, and various parameters influencing catalytic performance were investigated to attain maximum degradation efficiency. In a mere forty minutes, honey-mediated BiVO4 NPs demonstrated substantial degradation of the metronidazole drug under solar light, accomplished an optimal degradation of 71.04% under the reaction conditions of 0.4 mL H2O2, 0.5 g/L catalyst, and 10 mg/L metronidazole concentration. Furthermore, the scavenging test was used to identify the radicals implicated in metronidazole degradation in the presence of a BiVO4 photocatalyst. This study indicates that BiVO4 NPs have significant potential for ecological restoration using photocatalysis.